SWOT ANALYSIS (IFAS-EFAS) IN THE 7P MARKETING MIX STRATEGY TO INCREASE PATIENT REVISITS AT PRIVATE DENTAL CLINICS IN PEKANBARU - Rahmi, Sherly Firsta; Herniwanti, Herniwanti; Amalia, Rosi (HEARTY, 2026)
Competition among private dental clinics is increasing along with the increasing public awareness of the importance of dental and oral health. This condition requires dental clinics to not only focus on clinical services, but also implement appropriate service marketing strategies to retain patients and increase repeat visits. This study aims to evaluate the implementation of the 7P service marketing mix through a SWOT analysis approach in increasing repeat visits at Private Dental Clinic X Pekanbaru. The research method used is descriptive research with quantitative and qualitative analysis. Data collection was carried out through interviews with clinic management and internal and external factors were analyzed using SWOT analysis with the preparation of IFAS and EFAS matrices. The results showed that the strength factor had a total score of 48, while the weakness factor had a total score of 52. The opportunity factor obtained a total score of 52, while the threat factor had a total score of 50. The IFAS value obtained was -4 and the EFAS value was +2. Based on these results, the position of Private Dental Clinic X Pekanbaru is in Quadrant III (Weakness-Opportunity), which indicates that the clinic has quite large external opportunities but is still faced with internal weaknesses that need to be improved. The conclusion of this study is that the right strategy to implement is to minimize internal weaknesses by utilizing external opportunities. Therefore, the clinic is advised to improve its service system and strengthen its marketing strategy based on the 7P marketing mix to increase patient return visits and clinic competitiveness.